Onto scalable wireless ad hoc networks: adaptive and location-aware clustering - Conceição, Luís (2013)
Clustering is a widely used solution to provide routing scalability in wireless ad hoc networks. In the literature, clustering schemes feature different characteristics and purposes, however few schemes are context-aware. This work proposes a new solution called Distributed and Location-aware Clustering (DiLoC), a clustering scheme designed to operate in indoor environments, providing mechanisms to gather context location information in order to ease the maintenance of clusters, thus resulting in a stabler network topology in order to provide a scalable network topology for an efficient routing. DiLoC considers three distinct approaches, regarding the characteristics of the deployment environment, aiming to cover infrastructure-less, infrastructure and hybrid network scenarios. DiLoC was evaluated and compared with a similar clustering scheme, featuring the stability, amount of clustered nodes and network load. Included results demonstrate a scalable algorithm with a significant high stability.